De novo RNA sequence assembly during in vivo inflammatory stress reveals hundreds of unannotated lincRNAs in human blood CD14(+) monocytes and in adipose tissue - Xue, Chenyi (Physiol Genomics, 2017)
Long intergenic noncoding RNAs (lincRNAs) have emerged as key regulators of cellular functions and physiology. Yet functional lincRNAs often have low, context-specific and tissue-specific expression. We hypothesized that many human monocyte and adipose lincRNAs would be absent in current public annotations due to lincRNA tissue specificity, modest sequencing depth in public data, limitations of transcriptome assembly algorithms, and lack of dynamic physiological contexts. Deep RNA sequencing (RNA-Seq) was performed in peripheral blood CD14(+) monocytes (monocytes; average ~247 million reads per sample) and adipose tissue (average ~378 million reads per sample) collected before and after human experimental endotoxemia, an in vivo inflammatory stress, to identify tissue-specific and clinically relevant lincRNAs. Using a stringent filtering pipeline, we identified 109 unannotated lincRNAs in monocytes and 270 unannotated lincRNAs in adipose. Most unannotated lincRNAs are not conserved in rodents and are tissue specific, while many have features of regulated expression and are enriched in transposable elements. Specific subsets have enhancer RNA characteristics or are expressed only during inflammatory stress. A subset of unannotated lincRNAs was validated and replicated for their presence and inflammatory induction in independent human samples and for their monocyte and adipocyte origins. Through interrogation of public genome-wide association data, we also found evidence of specific disease association for selective unannotated lincRNAs. Our findings highlight the critical need to perform deep RNA-Seq in a cell-, tissue-, and context-specific manner to annotate the full repertoire of human lincRNAs for a complete understanding of lincRNA roles in dynamic cell functions and in human disease.